Fine Motor Skills In Early Childhood Education: A Bibliometric Analysis Of Scopus Publications (2021–2026) Using The Prisma Approach - Andrea Rodriguez; Angelica Sumba; Katherine Quezada (ALENA : Journal of Elementary Education, 2026)
Fine motor skills in early childhood education are closely associated with children’s cognitive, emotional, communicative, and pedagogical development. This study aimed to bibliometrically analyze the scientific production on fine motor skills in early childhood education indexed in Scopus during 2021–2026. A quantitative, descriptive, and documentary bibliometric study was conducted following the PRISMA approach. Data were retrieved from the Scopus database in June 2026 using English and Spanish search terms. A total of 29 documents met the inclusion criteria and were analyzed. Bibliometric indicators were obtained using the Scopus Analyze Search Results tool, and the data were organized for descriptive analysis. The results showed sustained growth in scientific production over the study period. Scientific articles represented 83% of the analyzed documents, followed by review articles (14%) and conference papers (3%). Social sciences accounted for 33% of the publications, while Indonesia, Australia, and Spain were the leading contributors. Ecuador showed limited scientific production. The findings indicate that fine motor skills constitute an expanding field of research and highlight the need to strengthen scientific production, international collaboration, and evidence-based pedagogical practices in Ecuador.